Primer on Chemical Vegetation Management in Florida Pine Plantations - Anna Osiecka; Jarek Nowak; Alan Long (EDIS)
This publication discusses factors that need to be considered to develop effective and safe herbicide prescriptions for pine plantation management. It also reviews some basic herbicide concepts and terminology important to understanding chemical vegetation management in pine plantations. Familiarity with this terminology is essential to understanding herbicide labels, which are legally binding documents for the herbicide use. This document is Circular 1477, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First Published: May 2005.